2018
DOI: 10.3390/molecules23010100
|View full text |Cite
|
Sign up to set email alerts
|

Increasing the Strength and Production of Artemisinin and Its Derivatives

Abstract: Artemisinin is a natural sesquiterpene lactone obtained from the Artemisia annua herb. It is widely used for the treatment of malaria. In this article, we have reviewed the role of artemisinin in controlling malaria, spread of resistance to artemisinin and the different methods used for its large scale production. The highest amount of artemisinin gene expression in tobacco leaf chloroplast leads to the production of 0.8 mg/g of the dry weight of the plant. This will revolutionize the treatment and control of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
15
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 26 publications
(16 citation statements)
references
References 110 publications
1
15
0
Order By: Relevance
“…Literature reports indicated that extraction of artemisinin has been carried out by different extraction methods: traditional solvent extraction, microwave-assisted extraction, ultrasound-aided extraction, and supercritical fluid extraction method using CO 2 as a solvent [20,46]. n -hexane [38], toluene [40], chloroform [41], petroleum ether [44], acetone, and ethanol [47] were the solvents most widely used for artemisinin extraction from Artemisia species.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Literature reports indicated that extraction of artemisinin has been carried out by different extraction methods: traditional solvent extraction, microwave-assisted extraction, ultrasound-aided extraction, and supercritical fluid extraction method using CO 2 as a solvent [20,46]. n -hexane [38], toluene [40], chloroform [41], petroleum ether [44], acetone, and ethanol [47] were the solvents most widely used for artemisinin extraction from Artemisia species.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, research interest in biotechnological approaches for enhanced artemisinin production in Artemisia have increased due to the global needs and low amounts of artemisinin and its derivatives in Artemisia plants [34]. Various biotechnological approaches such as the transformation of genes for production of artemisinin to cells of eukaryotic and prokaryotic organisms and to genetically engineered yeast were developed to enhance the production of artemisinin and its derivatives [35,36,37,38].…”
Section: Introductionmentioning
confidence: 99%
“…However, further studies are needed for its effects on the blood–brain barrier and during pregnancy, on whether it is safe to consume or not. For commercial and large-scale production of plant based important secondary metabolites, the expression of the genes that codes for the enzymes involved in their metabolic pathway into yeast or the tobacco plant offered an opportunity [28,29]. Gold et al expressed several genes that coded the different enzymes involved in the synthesis of steviosides in baker’s yeast, and the production of steviosides from glucose gave a good yield [30].…”
Section: Introductionmentioning
confidence: 99%
“…Due to its biological relevance, artemisinin, a tricyclic compound bearing a peroxide bridge, has been subject of extensive scientific investigations during the last decade [53][54][55][56][57][58][59][60][61][62][63]. In this context, Seeberger and co-workers successfully developed an ingenious continuous-flow process for the hemisynthesis of pure artemisinin from dihydroartemisinic acid (DHAA) [64,65].…”
Section: Review Artemisinin and Nanolobatolidementioning
confidence: 99%